Physiology and methodology of intermittent resistance training for acyclic sports - Casas, Adrián (2008)
Resistance training for acyclic sports has traditionally been carried out using training methods developed for cyclic sports. These methods were developed from the study of the physiological bases of maximum oxygen consumption (VO2max), prioritising "central" cardiovascular factors (cardiac) above "peripheral" factors (muscular) and omitting in-depth analysis of muscular behaviour during acyclic resistance. This article intends to: a) analyse certain physiological aspects needed to understand intermittent resistance exercise, b) define what intermittent resistance effort is, what its unique features are and how it differs from interval exercise, and c) develop a specific proposal for designing intermittent resistance training loads for acyclic sports.
Keywords: Training; Intermittent; Resistance; Sports; Acyclic